Nurse Educators' Background, Education, and Experience in Digital Competence Profiles: A Descriptive Comparative Cross‐Sectional Study in Four Countries - Pajari, Juha; Sormunen, Marjorita; Salminen, Leena; Elonen, Imane; Pasanen, Miko; Martin‐Delgado, Leandra; Camilleri, Michelle; Sollárová, Andrea; Haycock‐Stuart, Elaine; Saaranen, Terhi (Wiley-Blackwell, 2026)
Aim:
To identify and compare the digital competence profiles of nurse educators, the background variables associated with profiles, and the self-assessed level of digital competence in four European countries.
Design:
A descriptive comparative cross-sectional study.
Methods:
Data were collected from nurse educators (n = 263) in 36 nursing education organisations in Finland, Malta, Slovakia and Spain. Partitioning around medoids (PAM) clustering was used to identify competence groups, and descriptive and inferential statistics were used to examine the association of nurse educators' background variables.
Results:
The clustering analysis resulted in two nurse educator digital competence profile groups: high and moderate. The profiles differed based on completed pedagogical studies and teaching experience, with an emphasis on the high competence profile. Educators in the high competence profile group showed greater interest in using educational technology and self assessed their digital competence at a higher level compared to educators in the moderate competence profile group. Nurse educators' lowest digital competence was in the safe and responsible use of technology, such as knowing copyright laws.
Conclusion:
Despite the heterogeneous background of nurse educators, international continuing professional development needs in digital competence are identified. Nurse educators' continuing education should support the utilisation of technology through pedagogical approaches, and educators' competence in the safe and responsible use of technology (e.g., how to protect digital materials) must be enhanced in nursing education organisations.
Implications for the Profession:
This study highlights the need to further develop nurse educators' digital competence. Continuing professional development should target preparation in safe and responsible technology use and include pedagogical studies and mentoring from experienced peers.
Reporting Method:
The STROBE checklist was adhered to in reporting the results.
Patient or Public Contribution:
Each participating educational organisation assigned a contact person to distribute the survey to the nurse educators.